A Tradeoff Drives the Evolution of Reduced Metal Resistance in Natural Populations of Yeast - Chang, Shang-Lin (Public Library of Science, 2011)
Various types of genetic modification and selective forces have been implicated in the process of adaptation to novel or adverse environments. However, the underlying molecular mechanisms are not well understood in most natural populations. Here we report that a set of yeast strains collected from Evolution Canyon (EC), Israel, exhibit an extremely high tolerance to the heavy metal cadmium. We found that cadmium resistance is primarily caused by an enhanced function of a metal efflux pump, PCA1. Molecular analyses demonstrate that this enhancement can be largely attributed to mutations in the promoter sequence, while mutations in the coding region have a minor effect. Reconstruction experiments show that three single nucleotide substitutions in the PCA1 promoter quantitatively increase its activity and thus enhance the cells' cadmium resistance. Comparison among different yeast species shows that the critical nucleotides found in EC strains are conserved and functionally important for cadmium resistance in other species, suggesting that they represent an ancestral type. However, these nucleotides had diverged in most Saccharomyces cerevisiae populations, which gave cells growth advantages under conditions where cadmium is low or absent. Our results provide a rare example of a selective sweep in yeast populations driven by a tradeoff in metal resistance.